Recommendations for outpatient activity in COVID-19 pandemic - Palumbo Piergaspare (De Gruyter, 2021)
The spread of the COVID-19 disease substantially influenced the International Healthcare system, and the national governments worldwide had before long to decide how to manage the available resources, giving priority to the treatment of the COVID-infected patients. Then, in many countries, it was decided to limit the elective procedures to surgical oncology and emergency procedures. In fact, most of the routine, middle-low complexity surgical interventions were reduced, and the day surgery (DS) activities were almost totally interrupted. As a result of this approach, the waiting list of these patients has significantly increased. In the current phase, with a significant decrease in the incidence of COVID-19 cases, the surgical daily activity can be safely and effectively restarted. Adjustments are mandatory to resume the DS activity. The whole separation of pathways with respect to the long-stay and emergency surgery, an accurate preoperative protocol of patient management, with a proper selection and screening of all-day cases, careful scheduling of surgical organization in the operating room, and planning of the postoperative pathway are the goals for a feasible, safe, and effective resumption of DS activity.